Comprehensive circular RNA expression profiles and the tumor-suppressive function of circHIPK3 in ovarian cancer. (July 2019) - Teng, Fang; Xu, Juan; Zhang, Min; Liu, Siyu; Gu, Yuanyuan; Zhang, Mi; Wang, Xusu; Ni, Jing; Qian, Bing; Shen, Rong; Jia, Xuemei
Highlights: A total of 7333 circRNAs were found, of which 2431 were significantly upregulated and 3120 were remarkably downregulated. Six randomly selected circRNAs were validated by qRT- PCR, RT-PCR and sequencing after RNase digestion. Silencing of circHIPK3 promoted proliferation, migration, invasion and inhibited apoptosis of ovarian cancer cells. The circHIPK3-miRNA-mRNA axis was predicted as a possible mechanism using bioinformatic approaches. Abstract: Background: With the development of next-generation sequencing (NGS), thousands of circular RNAs (circRNAs) have been found. Many circRNAs have been verified to play vital roles in carcinogenesis. However, whether circRNAs engage in the development and progression of ovarian cancer remains to be clarified. Methods: We analyzed circRNA expression profiling in epithelial ovarian cancer (EOC) and normal ovarian tissues (NOT) using NGS and validated six randomly selected circRNAs via quantitative real-time-PCR (qRT-PCR), reverse-transcription PCR (RT-PCR) and Sanger sequencing after RNase treatment. CircHIPK3, the most abundant circRNA in our sequencing data, was further knocked down by siRNA. The circHIPK3 function in proliferation, invasion, migration and apoptosis of ovarian cancer cells and normal ovarian epithelial cells was analyzed via cell counting-kit 8 (CCK8), wound healing, transwell and flow cytometry analyses after circHIPK3 was efficiently silenced. Results: Altogether, we found 7333 circRNAs, of which 4505 (61.43%) were newly identified, 2431 were significantly upregulated and 3120 were remarkably downregulated. Six randomly selected differentially expressed circRNAs were examined in 18 EOC and 18 NOT. Furthermore, the results of RT-PCR and Sanger sequencing after RNase treatment confirmed head-to-tail back-splicing. Silencing of circHIPK3 promoted proliferation, migration, and invasion and inhibited apoptosis of ovarian cancer cells (A2780 and SKOV3) and normal ovarian epithelial cells (IOSE80). Additionally, the circHIPK3-miRNA-mRNA axis was predicted as the possible mechanism using bioinformatic approaches. Conclusions: We identified the circRNA expression profile in ovarian cancer tissues and further verified the existence and expression of six randomly selected differentially expressed circRNAs. Besides, we also found that circHIPK3 is an important regulator of ovarian cancer progression.